Goldmining and traditional leadership: Challenges to governing the small-scale gold mining sector in Suriname - Ine Apapoe (Caravelle)
Small-scale gold mining has become the main income for many traditional groups around the world in the past decades. Apart from the negative impacts on several aspects of tribal life, this sector also lead to challenges for tribal leadership in the governance of their society. This paper argues that it is crucial for the Surinamese state and tribal groups to focus on the challenges to govern the small-scale gold mining sector.